The Application of Posterior Plate in Tibial Plateau Fracture: A Case Report - Chilmi, Muhammad Zaim; Febrian, Firas ((JOINTS) Journal Orthopaedi and Traumatology Surabaya, 2024)
Backgrounds: Tibial plateau fracture is the most frequent type of fracture caused by motor-vehicle collision. This injury may or may not be associated with soft tissue injury, such as the knee's ligaments. Posterior tibial plateau fractures are a rare subtype that requires surgical intervention. This case report describes the outcome of posterior plating in treating a posterior tibial plateau fracture. Case report: A 41-year-old female patient came to the emergency room (ER) after being involved in a traffic collision. The patient underwent a thorough medical examination, which revealed the tibial eminence avulsion associated with the fracture of the head of the fibula. Surgical treatment was performed using a posterior approach through an inverted L-shaped incision. Discussion: Tibial plateau fractures are serious injuries that often require surgery. However, the decision to operate depends on several factors, including the morphology of the fracture, the patient's profile, the condition of the soft tissues, and the expected recovery of the articular surface and the axis of the limb. Conclusion: A surgical technique using a posterior approach through an inverted L-shaped incision with a small medial T-plate, lateral bone graft, and roof K-wire fixation demonstrates positive outcomes for treating closed posterior tibial plateau fractures and avulsion fractures of the tibial eminence.